2009
DOI: 10.1002/lary.20516
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear nerve diameter in normal hearing ears using high‐resolution magnetic resonance imaging

Abstract: CN diameter can be reliably measured at the IAC fundus. This study establishes normative radiographic data for the CN diameter. These data may be used to evaluate the cause and treatment prognosis in patients with sensorineural hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 7 publications
5
28
4
Order By: Relevance
“…There was no correlation between the diameter of the FN or CN with age. Table 5 shows the results of comparisons between the mean diameters of the CN in the present study and in the previous study using 3D-CISS, 11 and Table 6 shows those between the mean diameters of the CN and FN in the present study and in the previous study using 3D-DRIVE at 3T. 12 …”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…There was no correlation between the diameter of the FN or CN with age. Table 5 shows the results of comparisons between the mean diameters of the CN in the present study and in the previous study using 3D-CISS, 11 and Table 6 shows those between the mean diameters of the CN and FN in the present study and in the previous study using 3D-DRIVE at 3T. 12 …”
Section: Resultssupporting
confidence: 49%
“…We also compared mean diameters in the present study and previous studies, evaluating the normative diameters of the CN using 3D-CISS 11 and the CN and FN using 3D-DRIVE at 3T. 12 We found no statistical diŠerence between the diameters of the present study and the previous study using 3D-CISS, 11 although measurement locations were not necessarily identical (Table 5). On the other hand, diameters diŠered significantly between the present study and the previous study using 3D-DRIVE, 12 except for the CSA of the FN (Table 6).…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The CN is usually considered normal whenever its diameter is larger or equal to that of the FN [8], and several studies using SSFP MRI sequences have reported normal diameter values for the CN [3,8]. In the study of Nakamichi et al [3], the long and short diameters of the CN were approximately 1.35 ± 0.16 mm and 0.99 ± 0.18 mm when measured on the parasagittal image.…”
Section: Discussionmentioning
confidence: 99%